Taxonomic review and comparative morphology of the species of the genus Isistius Gill, 1864 (Chondrichthyes, Squaliformes: Dalatiidae) - Petean, Flávia de Figueiredo (2015)
The genus Isistius Gill, 1864, which belongs to the family Dalatiidae, currently has three valid species: Isistius brasiliensis Quoy & Gaimard, 1824, I. plutodus Garrick & Springer, 1964 and I. labialis Meng, Zhu & Li, 1985. The most common species, I. brasiliensis, has a wide geographic distribution, and can be found in subtemperate and tropical seas; a comparative analysis of specimens from different localities has never been done. This study has thoroughly analyzed the morphological variation of this species along its distribution, elucidating that it represents only one species, and I. labialis becomes a junior synonym. The other species, I. plutodus, is known from only few specimens, raising doubts about their validity since I. brasiliensis is widely distributed. A detailed comparative analysis of these individuals was undertaken to test the validity of this species. The representatives of all the nominal species within Isistius were studied, identifying them morphologically and re-describing them through more precise characters. Therefore, this study analyzed minutely the external morphology, such as coloration, dentition, dermal denticles, body proportions, and internal morphology, such as the skeleton and musculature, of the known species, also covering morphometric and meristic aspects, to better define the genus and provide relevant morphological subsidies that may integrate future phylogenetic analysis of genera within the family